2021
DOI: 10.3389/fpsyt.2021.640222
|View full text |Cite
|
Sign up to set email alerts
|

When Cannabis Use Goes Wrong: Mental Health Side Effects of Cannabis Use That Present to Emergency Services

Abstract: Cannabis use is a modifiable risk factor for the development and exacerbation of mental illness. The strongest evidence of risk is for the development of a psychotic disorder, associated with early and consistent use in youth and young adults. Cannabis-related mental health adverse events precipitating Emergency Department (ED) or Emergency Medical Services presentations can include anxiety, suicidal thoughts, psychotic or attenuated psychotic symptoms, and can account for 25–30% of cannabis-related ED visits.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 87 publications
0
24
0
1
Order By: Relevance
“…Whilst for some its use is not associated with harms, for others, especially heavy users, cannabis is associated with adverse health effects. Psychological adverse effects of cannabis use, such as anxiety, are well documented 4–6 . In the gastrointestinal system, the most well‐described manifestation of prolonged, heavy cannabis use is cannabinoid hyperemesis syndrome (CHS).…”
Section: Introductionmentioning
confidence: 99%
“…Whilst for some its use is not associated with harms, for others, especially heavy users, cannabis is associated with adverse health effects. Psychological adverse effects of cannabis use, such as anxiety, are well documented 4–6 . In the gastrointestinal system, the most well‐described manifestation of prolonged, heavy cannabis use is cannabinoid hyperemesis syndrome (CHS).…”
Section: Introductionmentioning
confidence: 99%
“…Cannabis industry advocates and individuals who use cannabis medicinally have emphasized cannabis use to achieve well-being and to cease use of other harmful substances (like opioids) (Barcott 2016;Dutcher 2018; Stukin 2019). On the other hand, prevention, treatment, and public health professionals have expressed concerns about widespread acceptance of a substance that can be addictive and that has been associated with a range of health risks, including increased dependence on and potential use of other substances (National Academy of Sciences 2017; Crocker et al 2021;Hall 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has shown that individuals are consuming more alcohol [ 35 – 38 ] and more cannabis [ 35 , 39 , 40 ] than they did before the pandemic. Such patterns in substance use may result in acute and chronic harms, such as injury, substance use dependence, and death [ 41 – 44 ]. People may be using more alcohol and cannabis to cope with anxiety, depression and loneliness experienced during the pandemic [ 45 – 47 ].…”
Section: Introductionmentioning
confidence: 99%